2014
DOI: 10.3389/fcimb.2014.00148
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic aspects of bacterial persisters

Abstract: Persister cells form a multi-drug tolerant subpopulation within an isogenic culture of bacteria that are genetically susceptible to antibiotics. Studies with different Gram negative and Gram positive bacteria have identified a large number of genes associated with the persister state. In contrast, the revelation of persister metabolism has only been addressed recently. We here summarize metabolic aspects of persisters, which includes an overview about the bifunctional role of selected carbohydrates as both tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 67 publications
2
76
0
2
Order By: Relevance
“…In this regard, it is also possible that CidB may be involved in persister formation, possibly through modulating cellular processes within a population. Persisters constitute a subpopulation of phenotypic variants that are genetically identical and metabolically slow-growing cells in a clonal bacterial population, largely in response to antibiotics (55)(56)(57). Recently, other stress responses and particularly oxidative stress were also reported to contribute to persister formation in Escherichia coli (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is also possible that CidB may be involved in persister formation, possibly through modulating cellular processes within a population. Persisters constitute a subpopulation of phenotypic variants that are genetically identical and metabolically slow-growing cells in a clonal bacterial population, largely in response to antibiotics (55)(56)(57). Recently, other stress responses and particularly oxidative stress were also reported to contribute to persister formation in Escherichia coli (58).…”
Section: Discussionmentioning
confidence: 99%
“…T/A modules are reported to play a central role in persister formation and/or the persister state (61)(62)(63). T/A modules are also known to function as "regulatory switches" under adverse conditions, allowing cells to enter a state that confers protection against a severe stressful condition or nutrient limitation, ultimately contributing to programmed cell death as a bacterial survival strategy (57,(64)(65)(66). Given that many genes related to PTS, the major route for internalization of carbohydrates in S. mutans, were differentially and highly regulated in the cidB mutant strain, it is also possible that the Cid/Lrg system fine-tunes cellular physiology during periods of stress to help preserve normal cellular homeostasis (e.g., during periods of "feast or famine" in oral plaque) through the potential T/A modules.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism has been emerging as a key modulator of persistence (5,28). Recent studies have demonstrated that metabolic stresses are important sources of persisters in both planktonic cultures and biofilms (29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these were less than 0.1% of the whole population. Much research has been focused on the exploration of the molecular keys linked to the persister phenomenon (37)(38)(39)(40)(41). Bertram and colleagues recently provided evidence that toxin-antitoxin (TA) systems play a key role in the regulatory network of persisters (42,43).…”
Section: Persister Cells As a Classical Model For Phenotypic Heterogementioning
confidence: 99%